Operational Characteristics of Microgrids with Electric Vehicles - Carlos L. Moreira (2014)
Microgrids are the basic building cells of a smart grid. They are assumed to be established at the low voltage distribution level, where distributed energy sources, storage devices, controllable loads, and electric vehicles are integrated and need to be properly managed. The microgrid cell is a very flexible system that can be operated connected to the main power network or autonomously, in a controlled and coordinated way. When operating in islanded mode, the MG relies on local energy storage to ensure the balance between generations and loads. However, when operating isolated from the main grid, the MG is more sensitive to power quality issues such as voltage unbalance, caused by the connection of single-phase loads and sources. In order to improve the MG emergency operation conditions, the EV should be envisaged as an active and flexible entity, providing to the MG additional distributed load or storage capacity under the vehicle-to-grid (V2G) concept. This chapter reviews the MG architecture considering EV and focuses on the impact of their active participation on the MG frequency regulation in emergency conditions (namely in islanding operating mode). Voltage unbalance issues during MG autonomous operation and the need for adopting voltage balancing mechanisms in specific power electronic interfaces are also discussed.